2016
DOI: 10.1158/1541-7786.mcr-15-0360
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin A2 and CDK2 as Novel Targets of Aspirin and Salicylic Acid: A Potential Role in Cancer Prevention

Abstract: Data emerging from the past 10 years have consolidated the rationale for investigating the use of aspirin as a chemopreventive agent; however, the mechanisms leading to its anti-cancer effects are still being elucidated. We hypothesized that aspirin’s chemopreventive actions may involve cell cycle regulation through modulation of the levels or activity of cyclin A2/cyclin dependent kinase-2 (CDK2). In this study, HT-29 and other diverse panel of cancer cells were used to demonstrate that both aspirin and its p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 58 publications
3
44
1
Order By: Relevance
“…Although reported that abnormal expression levels were found in multiple types of human malignancy and have potential as anticancer therapeutic targets [35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Although reported that abnormal expression levels were found in multiple types of human malignancy and have potential as anticancer therapeutic targets [35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results showed that aspirin could acetylate and inhibit glucose-6-phosphate dehydrogenase (G6PD), which catalyses the first reaction in the pentose phosphate pathway and is important for the regulation of oxidative stress [ 36 ]. For the mechanism of action in anti-cancer and chemoprevention activities, aspirin and salicylic acid can directly bind to CDK2 and down-regulate cyclin A2/CDK2 proteins [ 37 ] and inhibit CBP and p300 lysine acetyltransferase activity in vitro through direct competition with acetyl-Coenzyme A at the catalytic site [ 38 ]. These results revealed that the targets of aspirin and its metabolite are associated with metabolic function or immunity and are therefore involved in aging modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, aspirin may also indirectly activate AMPK through other processes [14]. It has been reported that aspirin and its metabolites regulate cyclin-dependent kinase (CDK) [15,16] and Wnt/β-catenin signaling [17,18].…”
Section: Ivyspringmentioning
confidence: 99%